(3GdQSGdI GdhGRYI dPhi GdCdHGH Yf aQW GdTc hGdEQJjGHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Gddge ROfG YdekG hGfaYfG jG cQej , fYhP HQMeI Gddg GdhGSYI ef JNHW GdTjGWjf hEdJHGSgG hbYJ Ydi eSGFd jXgQ di ef eYfGgG Cfg bO dYH GdTjWGf HYbdg cd edYH s
(3BNQgG (B:s
(3hCfG CSGd Gddg GdYXje GdPi HjOg CReI GdCHWjf GdNajI ef cd aJfI hHdjI , Cf jUdi Ydi eMeO hYdi Bdg GdWGgQjf JeJ s
(3CLGH HgG GdeDda Ydi SDGd UGQe GdOjf OGhO Hf CMeOs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdSejcs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs